If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2.27 = Log(x + 1) Reorder the terms: 2.27 = goL(1 + x) 2.27 = (1 * goL + x * goL) 2.27 = (1goL + goxL) Solving 2.27 = 1goL + goxL Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-1goL' to each side of the equation. 2.27 + -1goL = 1goL + -1goL + goxL Combine like terms: 1goL + -1goL = 0 2.27 + -1goL = 0 + goxL 2.27 + -1goL = goxL Add '-1goxL' to each side of the equation. 2.27 + -1goL + -1goxL = goxL + -1goxL Combine like terms: goxL + -1goxL = 0 2.27 + -1goL + -1goxL = 0 Add '-2.27' to each side of the equation. 2.27 + -1goL + -2.27 + -1goxL = 0 + -2.27 Reorder the terms: 2.27 + -2.27 + -1goL + -1goxL = 0 + -2.27 Combine like terms: 2.27 + -2.27 = 0.00 0.00 + -1goL + -1goxL = 0 + -2.27 -1goL + -1goxL = 0 + -2.27 Combine like terms: 0 + -2.27 = -2.27 -1goL + -1goxL = -2.27 Reorder the terms: 2.27 + -1goL + -1goxL = -2.27 + 2.27 Combine like terms: -2.27 + 2.27 = 0.00 2.27 + -1goL + -1goxL = 0.00 The solution to this equation could not be determined.
| -3x+5=x+21 | | -2x+14=-6 | | 4x+20=28 | | (2k-6)(7k-9)= | | 2x^2-68x=-546 | | y=0.5+-0.75x | | 3x+7=2x+2 | | S^2+a-42=0 | | 5a+3b-2a+4b= | | G*g= | | 5+3x=6+4x-5-2x | | M+m= | | 6(m+2)-10= | | 5(2x+5)=45 | | (X+2)/3=4 | | -7x-6y=-48 | | -5x-5y*6=25 | | -5x*6-5y*6=25 | | 3x+8y=-24 | | 8x-14=6x+2 | | -5x-5y=25*6 | | 12x-81=5 | | 0=x^2-169 | | 6x-11=-53 | | -35=34x+55y | | 5(y-1)=35 | | -6+4y=-4 | | 1.21v^2+0.068v=0 | | x+10y=80 | | m^2-10m+2=0 | | m^2=10m+24 | | 500=5e^9x |